Developing a Smart Quality Assurance Model for International Joint Training Programs in Vietnam - Kien, Nguyen Trung; Hoa, Le Thi (VNU Journal of Science: Education Research, 2026)
In the context of digital transformation and the internationalization of higher education, quality assurance (QA) is shifting from periodic, document-based evaluation towards continuous, data-informed and technology-enabled governance. This study develops and validates a Smart Quality Assurance (Smart QA) model for international joint training programs (IJTPs) in Vietnam. Addressing a key gap in the literature, the study conceptualizes Smart QA not as a set of isolated digital tools, but as an integrated governance framework connecting digital infrastructure (INF), internal QA governance (QA), learning analytics (LA), blockchain-enabled evidence verification (BC), implementation readiness (RDY), implementation barriers (BAR), student experience (STU), and quality outcomes (OUT). A sequential mixed-method design was adopted. In the qualitative phase, 15 experts in QA, digital governance, information systems and IJTP management were purposively selected to refine the constructs and assess item relevance, clarity and contextual suitability. In the quantitative phase, 620 valid responses were collected from 10 higher education institutions implementing IJTPs in Vietnam. Data were analysed using Cronbach’s Alpha, Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). The findings indicate good model fit and confirm the central mediating role of QA in translating digital infrastructure into quality outcomes. Learning analytics and blockchain-enabled verification positively affect OUT, while implementation barriers reduce effectiveness. Readiness shows a positive but statistically weak moderating tendency, whereas student experience positively strengthens the QA-OUT relationship in the extended analysis. The study contributes by theorizing Smart QA as a governance-based and learner-centred model, extending prior technology-focused approaches, and offering implications for digital evidence management, learner-centred QA design, and differentiated policy support for IJTPs in Vietnam.